The positive impact of vitamin C (Ascorbic Acid) utilisation in cancer treatment: a scoping review of published articles from the perspective of the in vitro studies - Mohammad Hamdi, Nurul Ain; Haris @ Harith, Muhammad Salahuddin; Harun Ismail, Ahmad Fahmi (UPM Press, 2021)
Survival benefit of patients with advanced cancer was reported with intravenous vitamin C administration. Nevertheless, a recent systematic review failed to support the clinically use of vitamin C in cancer patients due to the diversity of interventions and cancer type. This study aimed to provide a scoping review of vitamin C utilisation and its impact on cancer treatment from the perspective of in vitro studies. The review was conducted using predefined search terms in three scientific databases. 44 articles were retrieved with a total of 15 cancer types being studied from 2015 to 2020. The findings were classified into primary and secondary outcome. The primary outcome refers to chief consequences of vitamin C treatment, while the secondary outcome denotes the additional advantages generated as a result of the primary outcome, which occurs both in monotherapy and combination therapy. This review discussed the major mechanism of vitamin C as anti-cancer and its relation with the outcomes.